Development of drugs targeting hypoxia‐inducible factor against tumor cells with VHL mutation: Story of 127 years. Issue 4 (31st January 2023) - Takamori, Hajime; Yamasaki, Toshinari; Kitadai, Rui; Minamishima, Yoji Andrew; Nakamura, Eijiro
Abstract: Intratumoral hypoxia is associated with tumor progression and therapeutic resistance. The VHL tumor suppressor gene was identified in 1993, and later studies revealed that the gene product pVHL interacts with other proteins to form the VBC complex. The VBC complex functions as an E3 ubiquitin ligase and regulates the abundance of the α‐subunit of the transcription factor hypoxia‐inducible factor (HIF). Hypoxia‐inducible factor regulates thousands of genes required for cells to adapt and survive in hypoxic conditions, and thus pVHL plays a major role in oxygen‐sensing pathways. Patients with von Hippel–Lindau (VHL) disease, harboring a germline mutation of the VHL gene, develop renal cell carcinomas and a series of tumors showing hypervascular phenotypes. The extensive findings that have clarified the function of VHL have contributed to the development of novel first‐in‐human drugs, including belzutifan, a HIF‐2α inhibitor. The 2019 Nobel Prize in Physiology or Medicine was awarded to Dr. William G. Kaelin Jr., Dr. Peter J. Ratcliffe, and Dr. Gregg L. Semenza as researchers contributing to clarifying the mechanism of the oxygen‐sensing pathway of cells. The first report of VHL disease was in 1894, meaning the development of a specific drug for this disease took almost 125 years. In this article, we describe how researchers and clinician scientists successfully clarified the function of VHL and achieved a preclinical proof of concept to apply for clinical trials, key requirements for drug development. Abstract : pVHL forms an E3 ubiquitin ligase complex with Elongin B/C, Cul‐2, and Rbx‐1. The beta‐domain of pVHL recognizes one or two hydroxylated proline residue(s) in the NTAD of HIF alpha, binds to HIF alpha, and targets HIF alpha for ubiquitin‐dependent protein degradation at the proteasome.